2022
DOI: 10.1002/cssc.202200411
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Carbon‐Based Nanocatalysts and their Application in Catalytic Conversion of Renewable Platform Molecules

Abstract: The transformation of renewable platform molecules to produce value‐added fuels and fine‐chemicals is a promising strategy to sustainably meet future demands. Owing to their finely modified electronic and geometric properties, carbon‐based nanocatalysts have shown great capability to regulate their catalytic activity and stability. Their well‐defined and uniform structures also provide both the opportunity to explore intrinsic reaction mechanisms and the site‐requirement for valorization of renewable platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…Carbon‐based catalysts are receiving considerable attention in recent years as highly active and reusable low‐cost materials for multiple synthetic applications. Although carbonaceous materials can be generated from numerous organics after thermal treatment, they can also be prepared from inexpensive and renewable biomass and subsequently grafted with appropriate functional groups aimed at specific applications [1–4] . Such heterogeneous catalysts are progressively replacing homogeneous catalysts that exhibit undesirable side effects, such as corrosion derived from acid/basic wastes and they are also difficult to separate and recycle [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon‐based catalysts are receiving considerable attention in recent years as highly active and reusable low‐cost materials for multiple synthetic applications. Although carbonaceous materials can be generated from numerous organics after thermal treatment, they can also be prepared from inexpensive and renewable biomass and subsequently grafted with appropriate functional groups aimed at specific applications [1–4] . Such heterogeneous catalysts are progressively replacing homogeneous catalysts that exhibit undesirable side effects, such as corrosion derived from acid/basic wastes and they are also difficult to separate and recycle [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Although carbonaceous materials can be generated from numerous organics after thermal treatment, they can also be prepared from inexpensive and renewable biomass and subsequently grafted with appropriate functional groups aimed at specific applications. [1][2][3][4] Such heterogeneous catalysts are progressively replacing homogeneous catalysts that exhibit undesirable side effects, such as corrosion derived from acid/basic wastes and they are also difficult to separate and recycle. [5] Still, heterogeneous catalysis should face some challenging drawbacks associated to high loading, low catalytic performance, poor reusability, or high temperature for catalysis to occur.…”
Section: Introductionmentioning
confidence: 99%
“…The current focus lies in developing environmentally friendly synthetic procedures for the upgrading of the bio-derived platforms. In this context, carbon-based low-cost catalytic systems play a pivotal role (Sevilla et al, 2021;Chen et al, 2022), aligning with the principles of a circular and sustainable economy. Of particular importance is the utilization of biomass raw materials to prepare heterogeneous catalytic systems capable of efficiently converting LA to ethyl levulinate.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the catalytic activity of cathodes by altering the surface electron/proton concentration and chemical environment through transition metals is an impressive strategy. Yet, studies have demonstrated that heteroatoms, such as boron (B), phosphorus (P), and nitrogen (N), can also efficiently optimize the oxide material’s conductivity, sintering activity, acid–base properties (the electron/proton concentration), active oxygen concentration, and structural stability. However, P and N always optimize the cathode through bulk doping, as they escape by generating P 2 O 5 and NO x during the catalyst preparation process, making it difficult for them to stably exist on the cathode surface. Recently, Zhu et al found that B doped carbon nitride could form B-(OH) 2 acidic sites, which could activate styrene oxide through hydrogen bonding .…”
mentioning
confidence: 99%
“…In fact, acidic sites can be further divided into LAS and BAS. Wherein, LAS is the site that receives electrons and is considered unfavorable for ORR kinetics, and BAS is known as a proton acid, having a positive effect on water adsorption/dissociation, H spillover, and oxygen reduction reactions, which may be advantageous for the ORR process involving protons. ,,,, In order to further confirm the type of acid sites on the surface of the cathode, the pyridine-infrared (Py-IR) test results for PN and 0.5B-PN are shown in Figure c. Infrared adsorption bands at around 1445 and 1606 cm –1 are assigned to pyridine adsorbed on LAS; the bands at 1540 and 1633 cm –1 are related to BAS, and the peak at 1488 cm –1 belongs to an overlap of BAS and LAS. , In Figure c, the peaks of the 0.5B-PN sample at positions 1540 and 1633 cm –1 are significantly enhanced, while the signal peaks of LAS are markedly weakened.…”
mentioning
confidence: 99%